The potential of cell therapy in the treatment of univentricular heart defects - A. V. Nokhrin; A. V. Amosova; I. A. Cherepakhina; G. B. Belostotskaya; E. S. Kulemin; D. O. Ivanov (Вестник хирургии имени И.И. Грекова)
The single ventricle is a group of congenital heart defects, which even today remains the most difficult for surgical treatment and further patient care. The survival rate of patients with this defect remains relatively low despite a number of staged surgical interventions. A large percentage of mortality is observed in the interstage period due to the development of heart failure, the treatment of which is an urgent problem because standard therapy does not meet expectations. This article reviews the world literature on the application of an innovative method of heart failure correction – stem cell therapy. The main types of stem cells, their sources, mechanism of action, methods of their delivery to myocardium are also considered.